La pensée postmoderne et la criminologie - Brodeur, Jean-Paul (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1993)
This article is an attempt to investigate the various meanings of the words "postmodernity", "postmodernism" and "postmodern". ft also assesses the significance of these words and of the concepts that they express for criminology. The paper is divided in three parts. The first part tries to dispell important misunderstandings that have sprung in relation to postmodernism. The most significant of these is the belief that there is such a thing as a postmodernist "method" in the social sciences. The second part identifies the origin of the term "postmodern" and discusses various themes which are perceived to be characteristic of postmodern thought. These themes are: the present legitimation crisis, the internal reflexivity of scientific theory, discourse analysis and meta-language, social and cultural fragmentation and historical pessimism. The last part draws the consequences of the preceding analyses for the development of criminology.